PERBANDINGAN EFISIENSI DETEKTOR SINTILASI ORGANIK MENGGUNAKAN SINTILATOR ANTRASEN DAN NAFTALEN SERTA PENGARUH PENGGUNAAN KONTAK OPTIK TERHADAP EFISIENSI DETEKTOR PADA SPEKTROMETER BETA - Nur Indah Lestari; Evi Setiawati; Very Richardina (Youngster Physics Journal, 2015)
Research has been done to improve the efficiency of the manufacturing scintillator detector  in beta spectrometer. Detector efficiency is influenced by the type of scintillator, so that in this research will compare the efficiency of the detector using different types of organic scintillator. Scintillator used in this study are Anthracene and Naphthalene. In addition to comparing the efficiency of the scintillator, in this research will analyze the influence of the optical contact of silicone oil to the detector efficiency.Research done by pressing stainless steel mold containing the powder scintillator Anthracene and  Naphthalene. Pressure exerted is 86.6 kN / m2. Naphthalene and Anthracene scintillator made some thickness variations, start from 1 mm to 5 mm with a range of 0.5 mm. Then do the enumeration given 137Cs radiation  source on the surface of  the scintillator PMT (Photomultiplier Tube). To determine the effect of optical contact, given a silicone oil  layer between the surface of  the scintillator with PMT.The results of  the research showed that the efficiency of  the detector with Scintillator Anthracene larger than the scintillator Naphthalene. Scintillator detector efficiency with  Anthracene has a value of 99%, while the efficiency of the scintillator Naphthalene is 53.42%. Silicone oil as an optical contact effect on anthracene with thickness of 1 mm, while on the other the thickness of silicone oil had no effect. In Naphthalene, silicone oil effect on all thickness. It was seen from the increase of efficiency.Keyword : beta spectrometer, Detector efficiency, organic scintillator, optical contact of silicone oil